Differentiated learning and mathematical creative thinking: The use of Vos Viewer in literature mapping bibliometric analysis - Nindi Sri Rahayu; Muhamad Sofian Hadi (Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this study was to analyze publications on differentiated learning and mathematical creative thinking in order to increase aligned referrals. Data collection techniques used PoP (Harzing) software, while data analysis utilized VOS Viewer software. A total of 200 articles on differentiated learning and mathematical creative thinking were retrieved from Google Scholar data sources from 2013 to 2023 and were analyzed using a bibliometric analysis approach. The bibliometric analysis included sources, authors, and accuracy derived from the keywords